Analysis of Mural Paintings in Istria - Mazzocchin, Gian Antonio; Rudello, Danilo; Maraković, Nikolina Marić, Iva (2007)
Fragments of wall paintings from Istria, coming from the Basilica of Guran near Vodnjan, from the cemeterial Church of Saint Simeon in Guran and from the Benedictine monastery of Santa Maria Alta near Bale were studied. The analytical instrumental techniques used were Optical Microscopy, Scanning Electron Microscopy equipped with an EDS microanalysis detector, X Ray diffraction, FTIR infrared Spectroscopy and Raman Spectroscopy. Red and yellow pigments used in Guran and Bale have been derived from red and yellow Istrian bauxites, as already demostrated for works from 11th to 15th centruy. The blue pigment found in the paintings of the Bale Chapel is a lapislazzuli blue ; this fact confirms the literature data referring to the period from 11th to the 16th century. The materials and pigments used at Bale and Guran fit with the Istrian tradition and history of painting going back to the first Carolingian period.
Projekt MZOS
ENG